Kinematic, microphysical, and electrical structure and evolution of thunderstorms during the severe thunderstorm electrification and precipitation study (STEPS) - Wiens, Kyle Cameron, author (Colorado State University. Libraries, 2005)
Doppler-polarimetric radar and state-of-the-art lightning mapping measurements are used for detailed investigations of the kinematic, microphysical, and electrical evolution of several storms observed during the Severe Thunderstorm Electrification and Precipitation Study (STEPS). The focus is on determining what is different and/or unique about those storms that are dominated by positive cloud-to-ground (+CG) flashes. The set of case studies includes a +CG-dominant supercell, multicellular storms of varying severity that experienced a shift from -CG-dominance to +CG dominance, and an isolated storm that produced no CG flashes of either polarity despite frequent intra-cloud (IC) lightning. The parent charge structure of -CG-dominated storms differed significantly from that of +CG-dominated storms. In general, -CG-dominated storms exhibited the commonly observed normal tripole charge structure (positive over negative over positive charge), while the +CG-dominated storms exhibited what could be roughly de scribed as an inverted tripole structure (negative over positive over negative charge). Neither polarity of ground flash occurred without the presence of a lower charge region (lower positive charge in the case of -CG flashes, and lower negative charge in the case of +CG flashes). The one storm that produced no CG flashes exhibited an inverted dipole charge structure consisting of a vertically thin upper negative charge region and a deep lower positive charge region. The absence of a lower negative charge in this latter storm is likely the reason for its lack of +CG flashes. The total (IC plus CG) flash rate was found to be well-correlated with the convective development of each of the storms, with a particularly robust correlation between total flash rate and echo volume of radar-inferred graupel. Dramatic increases in total flash rate and vertical extent of the lightning flashes often accompanied strong surges in updraft and hail growth aloft, showing that total lightning measurements are a reliable proxy for convective intensity of thunderstorms and may have some utility as an indicator/predictor of severe weather.
Spring 2005.
Also issued as Kyle Cameron Wiens' dissertation (Ph.D.) -- Colorado State University, 2005.
Keywords: Thunderstorm electricity; Cloud electrification